Nonlinear sliding mode control of switched systems on continuously variable transmission shifting. (1st January 2013) - He, L.; Li, L.; Yu, L.Y.; Song, J.
The control of speed ratio on Continuously Variable Transmission (CVT) is one of the key problems for CVT development. In this paper, a nonlinear Sliding Mode Control (SMC) law of switched systems is designed and employed to control the CVT shifting. Because the CVT shifting control system contains discontinuous characteristics, the way of Filippov solution with discontinuous righthand side is used to design the sliding mode controller. Through the validation of simulation and on-board experiments, it can be concluded that the nonlinear SMC law is a better candidate to control the CVT shifting.